1970
DOI: 10.1111/j.1476-5381.1970.tb10366.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin uptake and metabolism by the perfused rat liver

Abstract: Summary1. The prostaglandins are C20 unsaturated fatty acids which exhibit diverse physiological effects of short duration. We have invesitigated the speed of removal of PGE1 and PGFia from the circulating blood and their subsequent metabolism by the isolated perfused rat liver. 2. Following either a single injection of radiolabelled PGE1 or PGFia into the hepatic artery or portal vein, or recirculation of prostaglandins through the liver for 2-5 h, the distribution of radioactivity within extracts of bile, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…As much as 85 to 90 % of PGE1 is inactivated by a single pass through the rat liver (Dawson, Jessup, McDonald-Gibson, Ramwell, and Shaw, 1970) and PGE1, E2 and F2, are also inactivated in the lungs of the guineapig,cat and dog (Piper, Vane, and Wyllie, 1970;Ferreira and Vane, 1967). Isoprenaline is also inactivated relatively rapidly by catechol 0-methyltransferase in the rat (Hertting, 1964) so it was necessary to devise a technique of infusing these compounds directly into the arterial blood supply of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…As much as 85 to 90 % of PGE1 is inactivated by a single pass through the rat liver (Dawson, Jessup, McDonald-Gibson, Ramwell, and Shaw, 1970) and PGE1, E2 and F2, are also inactivated in the lungs of the guineapig,cat and dog (Piper, Vane, and Wyllie, 1970;Ferreira and Vane, 1967). Isoprenaline is also inactivated relatively rapidly by catechol 0-methyltransferase in the rat (Hertting, 1964) so it was necessary to devise a technique of infusing these compounds directly into the arterial blood supply of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, PG are rapidly metabolized by hepatocytes [3, 48, 491. During one liver passage, more than 90% of exogenously added PG is degraded [50] (Piischel, G. P., Hulsmann, M. and Jungermann, K., unpublished results).…”
Section: Pg Receptor On Plasma Membranes Of Purified Hepatocytesmentioning
confidence: 96%
“…Dawson et al (10) suggested on the basis of isolated perfusion experiments with l4C-labeled PGE, rapid uptake and even decarboxylation of prostaglandin by rat liver tissue. Our data in dogs, are compatible with and add further weight to these investigations in cats and rats, that the liver appears to be an important site of inactivation of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%